Controlled and Targeted Drug Delivery by a UV‐responsive Liposome for Overcoming Chemo‐resistance in Non‐Hodgkin Lymphoma. (20th March 2015) - Li, Huafei; Guo, Kun; Wu, Cong; Shu, Ling; Guo, Shiwei; Hou, Jing; Zhao, Naping; Wei, Lixin; Man, Xiaobo; Zhang, Li
<x xml:space="preserve">Abstract</x> Although chemotherapy plays a vital role in treating non‐Hodgkin lymphomas, the clinical applications are limited because of intolerable side‐effects and multidrug resistance at the beginning or during the course of therapy. In this study, we successfully fabricated a CD20‐targeting immuno‐liposome based on 1, 2‐bis(10, 12‐tricosadiynoyl)‐sn‐glycero‐3‐phosphocholine (DC‐8, 9PC), which can form intermolecular cross‐linking through the diacetylenic group by ultraviolet irradiation. This immuno‐liposome showed appropriate size distribution, well‐defined regular spherical structure, favorable biocompatibility, high serum stability, and prolonged circulation time in blood vessels. The in and ex vivo experiments demonstrate enhanced tumor suppression abilities against both wild‐type and resistant non‐Hodgkin lymphomas for liposomal doxorubicin when compared with free drugs. The outstanding antitumor activities are attributed to the accumulation and retention of liposomal drugs in malignant tissues and cells, which are realized by the co‐operation of active targeting via antibody–antigen reaction and passive targeting via enhanced permeability and retention effect.